2016
DOI: 10.1001/jamapsychiatry.2015.2235
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Bright Light Treatment, Fluoxetine, and the Combination in Patients With Nonseasonal Major Depressive Disorder

Abstract: Bright light therapy is an evidence-based treatment for seasonal depression, but there is limited evidence for its efficacy in nonseasonal major depressive disorder (MDD). OBJECTIVE To determine the efficacy of light treatment, in monotherapy and in combination with fluoxetine hydrochloride, compared with a sham-placebo condition in adults with nonseasonal MDD. DESIGN, SETTING, AND PARTICIPANTS Randomized, double-blind, placebo-and sham-controlled, 8-week trial in adults (aged 19-60 years) with MDD of at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
159
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(166 citation statements)
references
References 44 publications
5
159
1
1
Order By: Relevance
“…This large antidepressant effect supports the theory of a causal role of phase delays in depression and more specifically, delayed melatonin offset. Combined, bright light and antidepressant provided even more benefit than either antidepressant or bright light alone (17). Indeed, the two treatments appeared possibly synergistic.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This large antidepressant effect supports the theory of a causal role of phase delays in depression and more specifically, delayed melatonin offset. Combined, bright light and antidepressant provided even more benefit than either antidepressant or bright light alone (17). Indeed, the two treatments appeared possibly synergistic.…”
mentioning
confidence: 95%
“…Growing proof of the antidepressant power of early morning bright light is now available. Most recently, Lam et al compared randomized early morning bright light treatment with a dummy treatment, with fluoxetine (a standard antidepressant), and with all-placebo treatment (17). Effects of early morning bright light alone over 8 weeks produced several times as much benefit as the antidepressant drug.…”
mentioning
confidence: 99%
“…18 Light therapy is generally well tolerated, 17 with common side effects being eye strain, headache, agitation, nausea, and sedation. 19 Since 2009, 2 meta-analyses, 16,20 4 systematic reviews 17,19,21,22 and 3 RCTs [23][24][25] have been generally confirmatory of recommendations in the 2009 guidelines (see Suppl. Table S1).…”
Section: What Is Light Therapy? How Effective Is Light Therapy For Thmentioning
confidence: 94%
“…20 In addition, an RCT reported that LT monotherapy and LT combined with fluoxetine were superior to placebo in nonseasonal MDD, with the combined treatment showing the most consistent effects. 23 Similarly, medication paired with chronotherapeutic techniques (LT, sleep deprivation, and sleep time stabilization) led to superior remission rates in nonseasonal MDD compared to medication combined with exercise at both 9-week and 29-week follow-up. 24,27 In summary, the updated evidence continues to support LT as a first-line monotherapy for seasonal depression and as a second-line monotherapy or adjunctive treatment for mild to moderate nonseasonal MDD ( Table 2).…”
Section: What Is Light Therapy? How Effective Is Light Therapy For Thmentioning
confidence: 98%
“…LT has been employed for the treatment of seasonal affective disorder (SAD) in particular [5,6]. However, studies have also been conducted on the effectiveness of LT for other psychiatric disorders, such as non-seasonal major depressive disorder [7,8], premenstrual dysphoric disorder [9,10], antepartum depression [11], circadian disturbances in shift workers [12,13], jet lag syndrome [14,15], alcohol withdrawal syndrome [16], negative symptoms in schizophrenia [17,18], cognitive and behavioural symptoms in Alzheimer's disease [19], and Parkinson's disease [20,21]. …”
Section: Introductionmentioning
confidence: 99%